Connecting People? Understanding Media's Role as Democratic Resources for People in Digitally Advanced Local Environments. Issue 4 (20th April 2020) - Olsen, Ragnhild Kristine
Abstract: Communication abundance in the digital sphere has raised concern over audience fragmentation and the declining capacity of general news media to shape common experiences and promote shared discourses required by a well-functioning local democracy. Based on the concept of mediated public connection this paper offers an analytical framework to investigate how people orient themselves to a local public world through media in high-choice, digitally advanced information environments. Two analytical dimensions of people's media use – practice and perception – are tested on survey data from Norway ( N  = 1692) using a network analysis approach combined with media experience data. The study finds substantial convergence in use of different online and offline media with the largest audience overlap occurring between online local and regional newspapers and Facebook. These digital players represent the backbone of the local media environment under study. Overall, citizens' experiences with different media as democratic resources for their local public life are not very strong and weaker for online media than for their offline editions.